Major publications in the critical care pharmacotherapy literature: January–December 2013. (1st February 2015) - Rech, Megan A.; Day, Sarah A.; Kast, Jenna M.; Donahey, Elisabeth E.; Pajoumand, Mehrnaz; Kram, Shawn J.; Erdman, Michael J.; Peitz, Gregory J.; Allen, John M.; Palmer, Allison; Kram, Bridgette; Harris, Serena A.; et al.
Abstract: Purpose: Ten recently published articles with important implications for critical care pharmacotherapy are summarized. Summary: The Critical Care Pharmacotherapy Literature Update (CCPLU) group is a national assembly of experienced intensive care unit (ICU) pharmacists across the United States. Group members monitor 25 peer-reviewed journals on an ongoing basis to identify literature relevant to pharmacy practice in the critical care setting. After evaluation by CCPLU group members, selected articles are chosen for summarization and distribution to group members nationwide based on (1) applicability to critical care practice, (2) relevance to pharmacy practitioners, and (3) quality of evidence or research methodology. Hundreds of relevant articles were evaluated by the group during the period January–December 2013, of which 98 were summarized and disseminated nationally to CCPLU group members. Among those 98 publications, 10 deemed to be of particularly high utility to critical care practitioners were included in this review. The 10 articles address topics such as rapid lowering of blood pressure in patients with intracranial hemorrhage, adjunctive therapy to prevent renal injury due to acute heart failure, triple-drug therapy to improve neurologic outcomes after cardiac arrest, and continuous versus intermittent infusion of β-lactam antibiotics in severe sepsis. Conclusion: There were many important additions to the critical care pharmacotherapy literature in 2013, including an updated guideline on the management of myocardial infarction and reports on advances in research focused on improving outcomes in patients with stroke or cardiac arrest and preventing the spread of drug-resistant pathogens in the ICU.